2016
DOI: 10.1016/j.jamcollsurg.2016.01.060
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Cholangitis and Future Liver Remnant Volume Determine the Risk of Liver Failure in Patients Undergoing Resection for Hilar Cholangiocarcinoma

Abstract: Background The highest mortality rates after liver surgery are reported in patients who undergo resection for hilar cholangiocarcinoma (HCCA). In these patients, postoperative death usually follows the development of hepatic insufficiency. We sought to determine the factors associated with postoperative hepatic insufficiency and death due to liver failure in patients undergoing hepatectomy for HCCA. Study Design This study included all consecutive patients who underwent hepatectomy with curative intent for H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
121
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(131 citation statements)
references
References 42 publications
4
121
1
5
Order By: Relevance
“…The current results indicated that the short-term surgical and postoperative outcomes of the group that directly underwent surgery were comparable to those of the group that underwent PBD. This finding is consistent with the results of previous studies and meta-analyses (12)(13)(14). Several studies have found that PBD increased the risk of postoperative complications and infections (15)(16)(17), but our data did not demonstrate this.…”
Section: Discussionsupporting
confidence: 91%
“…The current results indicated that the short-term surgical and postoperative outcomes of the group that directly underwent surgery were comparable to those of the group that underwent PBD. This finding is consistent with the results of previous studies and meta-analyses (12)(13)(14). Several studies have found that PBD increased the risk of postoperative complications and infections (15)(16)(17), but our data did not demonstrate this.…”
Section: Discussionsupporting
confidence: 91%
“…Liver resection for biliary tract cancer is reported to be associated with high rates of morbidity (22–55%) and mortality (3.3–11%), even at high-volume centers [5, 11, 12]. PHLF is the most common cause of postoperative death.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also shown a clear correlation between drainage-induced cholangitis and mortality after resection and between drainage failure and survival in the palliative setting. 7,10,20 The overall relatively high therapeutic failure rate and inadequate drainage of the FLR in the study period resulted in exposure of patients to multiple drainage procedures and, consequently, to unnecessary risks of complications. The observation that the complication risks of biliary drainage were comparably as high in the regional hospitals as in experienced hands in our center, underscores the complex nature of drainage in hilar obstructions.…”
Section: Discussionmentioning
confidence: 99%
“…Patients had a median age of 66 years, included 104 males (65.8%) and presented with jaundice in the majority of cases (75.9%). Median time interval between first suspicion of PHC at the regional center and referral to our MDT was 11 days (IQR: [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. In 39 of 158 cases (24.7%), the time to referral was 21 days or more.…”
Section: Study Populationmentioning
confidence: 99%